Prognostic analysis of different postoperative adjuvant therapies for patients with hepatocellular carcinoma after radical resection with high-risk recurrence factors: a multicenter real-world retrospective study - Zhao, Zejin; Xiao, Yue; Su, Chen-guang; Zhao, Hui; Li, Jian; Liu, Jinlong (Frontiers in Immunology, 2025)
BackgroundHepatocellular carcinoma (HCC) is one of the most common malignant tumors worldwide, with high postoperative recurrence rates significantly limiting long-term survival, particularly in patients with high-risk features such as large tumor diameter (≥5 cm), multiple tumors (≥3 nodules), microvascular invasion (MVI), or portal vein tumor thrombus (PVTT). There is still considerable controversy about the efficacy of adjuvant therapy after liver resection (LR) in improving the prognosis of HCC patients with high risk of recurrence and its therapeutic efficacy in different high-risk subgroups.Materials and methodsThis multicenter retrospective study included 300 patients with high-risk HCC who underwent liver resection in four medical institutions in China from January 2015 to April 2024, including 101 patients in the LR group and 199 patients in the LR+ postoperative adjuvant therapy group.ResultsDuring follow-up, 178 patients (59.3%) died. OS was significantly better in the LR plus adjuvant therapy group than in the LR alone group (entire cohort: HR = 0.55, 95% CI: 0.39–0.76, P<0.001; matched cohort: HR = 0.47, 95% CI: 0.32–0.71, P<0.001). The median OS in the matched cohort was 32.1 months (95% CI: 25.4-38.8) for the adjuvant group versus 18.5 months (95% CI: 14.2-22.8) for the LR group. In the matched cohort, 1-, 3-, and 5-year OS rates were 82.2%, 46.0%, and 20.2% for the adjuvant group versus 63.4%, 33.1%, and 17.2% for the LR group. DFS was also significantly prolonged in the adjuvant group (HR = 0.43, 95% CI: 0.29–0.65, P< 0.001), with a median DFS of 15.3 months (95% CI: 11.9-18.7) compared to 8.1 months (95% CI: 6.5-9.7) in the LR group, and 1-year DFS of 53.4% vs 30.9%. Multivariate analyses identified AFP, ALB, tumor diameter, PVTT, TACE, and adjuvant therapy as independent predictors of OS, while AFP, multiple tumors, MVI, PVTT, TACE, and adjuvant therapy were associated with DFS. Subgroup analysis showed that TACE offered significant benefit (OS: HR = 0.54; DFS: HR = 0.55), and TKI therapy also demonstrated improved outcomes (OS: HR = 0.58; DFS: HR = 0.58).ConclusionPostoperative adjuvant therapy provides significant survival benefits for HCC patients with high risk of recurrence, with TACE therapy demonstrating the greatest efficacy. These findings underscore the importance of individualized postoperative management in this population.